PENGARUH BUDAYA KEWIRAUSAHAAN DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA INSTITUT BISNIS DAN INFORMATIKA KWIK KIAN GIE DAN UNIVERSITAS BAKRIE - Albertus Ivan Hendrata (Jurnal Ekonomi Perusahaan, 2020)
This research aims to determine the influence of entrepreneurship culture (perceived appropriateness, perceived consistency, and perceived effectiveness) and entrepreneurship education on entrepreneurship intention among students. It is also purposed to test whether entrepreneurship culture mediates the effect of entrepreneurship education on entrepreneurship intention among students. The research was conducted among 200 students from Bakrie University and Institut Bisnis dan Informatika Kwik Kian Gie who had completed an entrepreneurship course and did not yet have a business. The research design used is descriptive quantitative research. The data analysis technique uses multiple linear regression analysis. The result showed that all independent variables (perceived appropriateness, perceived consistency, perceived effectiveness, entrepreneurship education) had a positive effect on entrepreneurship intention among students. In addition, the entrepreneurship culture mediates the relationship of the influence of entrepreneurship education to entrepreneurship intention among students. Keywords: perceived appropriateness, perceived consistency, perceived effectiveness, entrepreneurship education, entrepreneurship intention.